Designing Automatic Safe Security Devices Using Microcontroller Based RFID and Fingerprint - Angga Saputra; Yohandri Yohandri (Journal of Experimental and Applied Physics, 2023)
A safe is a fire-resistant metal cabinet or box that is usually used by the owner to store valuables (such as money, valuable papers, jewelry, etc.) from thieves/burglars. Safes are generally in the form of cubes/blocks or cylinders. Safes are usually wall-mounted, as well as large room-shaped safes. But not a few also know the weaknesses of the security so that the safe is easily stolen. Based on the description above, in this study the authors are interested in designing an automatic safe system using a fingerprint microcontroller-based in the main system, this automatic safe is regulated by the Arduino Atmega 2560 microcontroller with the Arduino IDE programming language. The safe system automatically works when the user enters the fingerprint and RFID tag correctly, the safe will open. Based on data analysis, it is obtained in the form of a mechanical tool in the test, the characteristics of the sensor, accuracy and precision of the tool are obtained. The characteristics of the sensor can be seen from the fingerprint sensor and RFID sensor. The accuracy value of the sensor on the tool, namely the fingerprint sensor and RFID sensor, the accuracy is very good, the accuracy of the RFID sensor voltage is 99.73% while the accuracy value of the RFID sensor has very good accuracy.